Correlation of x-ray vector radiography to bone micro-architecture - Schaff, Florian; Malecki, Andreas; Potdevin, Guillaume; Eggl, Elena; Noel, Peter B.; Baum, Thomas; Garcia, Eduardo Grande; Bauer, Jan S.; Pfeiffer, Franz (Scientific Reports, 2014)
Besides the overall mass density, strength of trabecular bone depends significantly on its microstructure. However, due to dose constraints in medical CT imaging, it is impossible to gain sufficient information about very fine bone structures in vivo on the micrometer scale. Here we show that a recently developed method of X-ray vector radiography (XVR), an imaging method which uses X-ray scattering information to form an image, allows predictions on the bone microstructure without the explicit need to spatially resolve even individual trabeculae in the bone. We investigated thick human femoral bone samples and compared state-of-the-art μCT data with XVR imaging. A model is presented which proves that XVR imaging yields information directly correlated with the trabecular microstructure. This opens up possibilities of using XVR as a tool to help early diagnosis of bone diseases, such as osteoporosis.
CRIS-Team Scopus Importer:2023-03-08